Bunuel wrote:
(2) c = d. The question becomes: does (c-2)(c-2) = 4 ? --> does c^2 = 8. We don't know that, so this statement is not sufficient.
Answer: A.
Thanks for answering
Bunuel but here's my issue, and if my arithmetic is to blame please point it out, but shouldn't (c-2)(c-2) become:
C(squared) - 2C - 2C + 4 = 4
C(squared) - 4C = 0
C(squared) = 4C
C = 4?
(edit for clarification) - And if we know C = 4, and C and D are equal, then if we plug that into the question then we can answer whether it is equal to 4 or not (the answer being yes), no?